Effectiveness of an Educational Program on Nurse’s Knowledge & Practices Toward Uses of Defibrillation Cardioversion Shock at Critical Care Unit in Imam Al-Hussein Teaching Hospital - Dahi, Safaa Jalil; Ahmed , Sabah A. (International Journal of Psychosocial Rehabilitation, 2020)
Objective: To evaluate the effectiveness of an educational program in knowing nurses towards the use of cardiac defibrillation shock for patients with arrhythmias, and to evaluate the effectiveness of the educational program on the practice of nurses who use defibrillation shock for patients with arrhythmias in the critical care unit, and to identify the relationship between effectiveness Educational program and demographic characteristics (age, level of education, address, years of service) for nurses. Methodology: A quasi- experimental study conducted in the critical care units (cardiac resuscitation, pulmonary resuscitation, surgical resuscitation) at Imam Hussein Teaching Hospital, from(26th November 2019 To 10th May 2020) A purpose sample (non-probability) consisting of (60) nurses was tested. And a nurse is divided into two groups (30) nurses for the case study group, and 30 nurses for the control group. The data was collected in two phases: first the baseline data (before any overlap was made to the study group) and 21 days after the implementation of the educational program of the study group the test was conducted after the program, for the nurses’ knowledge, and 14 days after applying the educational program of the study group For their practices. The reliability of the internal consistency was achieved by applying the alpha correlation Coefficient (r=0.85) which was statistically acceptable. The data were analyzed by applying descriptive and inferential data . Results: The results of this study shows that there is a highly significant differences related to nurses’ knowledge and practices regarding Uses of Defibrillation Cardio version Shock at Critical Care Unit; between pre & post-test in the study group. with no statistically significances differences between demographics variables ( age, gender, years of service in nursing) ,while there is statistically significances differences between demographics variables (educational level and years of service in critical care units) and effectiveness of educational program for nurse`s. Conclusion: Nurses’ knowledge and practices regarding Uses of Defibrillation Cardio version Shock at Critical Care Unit, has been improved after implementation of the educational program in the study group, which reveal that the effectiveness of the provided program was highly beneficial. Recommendations: Orientation program should be utilized for newly graduated nurses in critical care units to improve their knowledge and practice., Nurses in critical care units should updating their knowledge and practice through frequent attending seminars, and conferences based on their needed assessment. , Continuous educational program for theses nurses concerning any emergency situation in the critical care units.